Iniciação à docência na UFMT : contribuições do PIBID na formação de professores de química - Dantas, Larissa Kely (2013)
This study presents a research on the potential of the Institutional Program Initiation Scholarship to Teaching (Pibid) for teacher training. In the current context and challenges educional accented front of a profession with little social recognition and, consequently, low attractiveness to young people entering the university, teacher training has become in the course of the last decades a topic of social relevance. In this scenario the Pibid has become very important public policy of valuing teaching, enabling undergraduate participation in their field of work, from the beginning of its formation, through activities that enable interaction with teachers and students of education Basic and articulation between universities and schools. The central objective of this research is to examine in what ways the project Pibid / UFMT contributed to training and initiation to teaching participants subproject of Chemistry - Notice 2007. With this intention of this study is characterized as a qualitative research, with elements of case study and document analysis. Are used as instruments to collect data: questionnaires, semi-structured interviews and documentary analysis, with emphasis on subproject of Chemistry, institutional reports and official documents. The subjects selected for this research were: eleven alumni, two supervisors and area coordinator both Subproject Chemistry, 2007 announcement. After analysis of primary data collected, we see the need to return to the field of study to investigate a possible entanglement between the goals and purposes of Pibid and Supervised training. The results showed that, from carrying out the activities proposed in the subproject, there was growth in academic scholarship, which tends to break with the logic discipline, and that the link between theory and practice in teaching real environment favors the construction of identity teaching. The results also point to the Pibid as a program that creates opportunities for changes in existing training models. We also note with speech analysis of the subjects that Pibid is understood as a program developer for improving teacher education through integration between university and school, providing opportunities for future teacher understanding and reflection on the teaching profession and also about school reality with the development of teaching units that prioritize the inclusion of different materials and innovative teaching approaches in science education. About the possible entanglement between the goals and purposes of Pibid Supervised training and we ascertain that there is a fine line between dimensions: practical, theoretical and documentary, as both have a systematic academic inducer for teacher training, but the main difference is that the licensing stage arises in the teaching function, experiencing their professional nature, discusses with colleagues within the context of their initial training. The Pibid collaborates with this, however, does not replace the dynamic stage and goals, are just complementary.